2020
DOI: 10.1002/ppul.25161
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐synchronized NIPPV with double‐inspiratory loop cannula: An in vitro study

Abstract: Background: Although short binasal prongs (SBP) are the most common interface for noninvasive ventilation, the "double-inspiratory loop cannulas" (DILC) have recently been introduced into many neonatal intensive care units. DILC show advantages over SBP, including reduced nasal trauma and increased comfort. However, their higher intrinsic resistance may compromise ventilation. Our aim was to test a new, low resistance DILC interface. Methods: A test lung was programmed to simulate preterm neonates (500-2000 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Green et al showed that nasal mask has the lowest resistance, short bi‐nasal prongs have high resistance at high flow and small size, while RAM® cannula has the highest resistance. Several in‐vitro studies confirmed that RAM® cannula imposes a significantly higher resistance compared with other nasal interfaces 14,15,18 . In a bench study, Iyer et al documented a limited transmission of both PEEP and PIP to the lung with RAM® cannula during NIPPV.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Green et al showed that nasal mask has the lowest resistance, short bi‐nasal prongs have high resistance at high flow and small size, while RAM® cannula has the highest resistance. Several in‐vitro studies confirmed that RAM® cannula imposes a significantly higher resistance compared with other nasal interfaces 14,15,18 . In a bench study, Iyer et al documented a limited transmission of both PEEP and PIP to the lung with RAM® cannula during NIPPV.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to underline that RAM® cannula should not be used with no leaks (e.g., 100% nares occlusion and mouth sealed), as per manufacturer's instructions. Indeed, the use of RAM® cannula with no leaks obliges the infant to expire through the RAM® cannula itself, increasing the expiratory resistance and the risk of rebreathing 18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations